ANALISIS PENGARUH STRES KERJA DAN KOMPENSASI TERHADAP TURNOVER INTENTION KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI (Studi Kasus pada Karyawan SMK Leonardo Klaten) - Yuliantoro, Septian Eko; Wahyudi, Amin; Suprayitno, Suprayitno (Universitas Slamet Riyadi, 2019)
This research aims to determine the significant influence between: (1) Job Stress on Job Satisfaction, (2) Compensation on Job Satisfaction, (3) Job Stress on Turnover Intention, (4) Compensation on Turnover Intention, (5) Job Satisfaction on Turnover Intention of SMK Leonardo Klaten employees. This study also aims to determine: (6) the effect of Job Stress on Turnover Intention with Job Satisfaction as a mediating variable, (7) the effect of Compensation on Turnover Intention with Job Satisfaction as a mediating variable. The population is the employees of SMK Leonardo Klaten as many as 62 persons. Sampling uses a sampling jenuh technique where all populations are taken as research samples, as many as 62 persons. Data collection techniques using questionnaires through validity test and reliability test. The analysis technique uses the classic assumption test, path analysis, and sobel test. The results of the analysis show: (1) A significant effect of work stress variable on job satisfaction. (2) A significant effect of the compensation variable on job satisfaction. (3) A significant effect of the work stress variable on turnover intention. (4) The compensation has no significant effect on Turnover Intention. (5) Job satisfaction has no significant effect on Turnover Intention. (6) Job satisfaction does not mediate the effect of work stress on turnover intention. (7) Job satisfaction mediates the effect of compensation on turnover intention.